2023
DOI: 10.1186/s12876-023-02912-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel long non-coding RNA XLOC_004787, is associated with migration and promotes cancer cell proliferation by downregulating mir-203a-3p in gastric cancer

Renjie Miao,
Zhendong Yao,
Bingheng Hu
et al.

Abstract: Background Long noncoding RNAs (lncRNAs) have been identified as important regulatory factors implicated in a wide array of diseases, including various forms of cancer. However, the roles of most lncRNAs in the progression of gastric cancer (GC) remain largely unexplored. This study investigates the biological function and underlying mechanism of a novel lncRNA, XLOC_004787 in GC. Methods The location of XLOC_004787 in GES-1 cells and HGC-27 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In various major malignancies, ncRNAs are frequently thought to be oncogenic and anti-oncogenic (Slack and Chinnaiyan 2019 ). Ren et al revealed that the lncRNA XLOC_004787 enhances cancer cell proliferation in GC via down-regulating mir-203a-3p (Miao et al 2023 ). According to Liu et al, circRNA CDR1 acted as a novel diagnostic and prognostic biomarker for GC (Li et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In various major malignancies, ncRNAs are frequently thought to be oncogenic and anti-oncogenic (Slack and Chinnaiyan 2019 ). Ren et al revealed that the lncRNA XLOC_004787 enhances cancer cell proliferation in GC via down-regulating mir-203a-3p (Miao et al 2023 ). According to Liu et al, circRNA CDR1 acted as a novel diagnostic and prognostic biomarker for GC (Li et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%